Stevioside ameliorates hyperglycemia and glucose intolerance, in a diet-induced obese zebrafish model, through epigenetic, oxidative stress and inflammatory regulation - ALTURFAN, EBRU IŞIK; AK, ESİN (Elsevier Ltd, 2022)
Obesity is an independent risk factor for type 2 diabetes and epigenetic regulatory mechanisms affect obesity-related mechanisms. Due to weight gain concern in society, artificial sweeteners with no nutritional value have been increasingly consumed. Stevia is a sweet natural glycoside and a calorie-free sweetner extracted from the leaves of Stevia rebaudiana Bertoni and used as a substitute for artificial sweetners. This study evaluates the effects of stevioside on glucose tolerance, epigenetic and metabolic regulators of insulin resistance, oxidant-antioxidant status and tissue histology in a diet-induced obese (DIO) zebrafish model. After 15 days of overfeeding body weight, and fasting blood glucose, lipid peroxidation and nitric oxide levels and the expressions of fbf21, lepa, ll21, tnfα were elevated, where as there was impaired glucose tolerance and lower superoxide dismutase and glutathione S-transferase activities, dnmt3a expression which is an epigenetic tool of insulin resistance. Beneficial effects of stevioside were observed on glucose tolerance, oxidative stress and inflammatory mediators linking obesity to insulin resistance and its epigenetic regulation, in DIO model. © 2022 Asia Oceania Association for the Study of Obesity
Keywords: Diet-induced obesity; Glucose intolerance; Oxidative stress; Stevioside; Zebrafish